Analisis Produktivitas Mesin Filling Auto Cup Sealer 1 dengan Metode Overall Equipment Effectiveness pada PT. Prima Kemasindo - Nurhayati Nurhayati; Dene Herwanto; Hamdani Hamdani (Jurnal Serambi Engineering, 2021)
The high level of downtime on the ACS 1 filling machine at PT. Prima Kemasindo causes the production process to be not optimal on the machine. The purpose of this study is to identify the maintenance system on the ACS 1 filling machine and measure the productivity level of the ACS 1 filling machine in the period from January to March 2021. This research is applied research using the Overall Equipment Effectiveness (OEE) method. The data used in this study are primary and secondary data obtained from company reports as well as interviews and observations. The results obtained in this study are the Overall Equipment Effectiveness (OEE) value of the ACS 1 filling machine for the period January 98.0%, February 98.5%, March 95.2%, and the average OEE value for the January-March period is 97.2 %. Then from the analysis of Six Big Loses, it is known that the highest loss elements are Idling and Mirror Stoppages and Reduced Speed. Based on the results of the fishbone diagram, it is known that the cause of Idling and Mirror Stoppages and Reduced Speed consists of several factors, namely humans, machines, materials, and methods. Several efforts can be made to increase the effectiveness of the use of machines, namely periodic replacement of machine maintenance, periodic operator training, and training on operator self-awareness, the importance of supervision, and operators must always supervise machine parts.